A Study Of The Relationship Between Indicators And Public Donation Intention In Penang: A Perspective Of Planned Behavior Theory With Inclusion Of Some Cognitive Factors - Ho, Eng Ling (2012)
The continuous survival of charity organizations has been challenged with increasing demand for their services as well as diminishing government supports, leading to ever-increasing need for charity giving (Sargeant, Lee, and Jay, 2002). Scenario in Malaysia is similar, where an assessment made through local charity website, www.hati.org.my shows charitable organizations are challenged to raise significant donation to cover high demand for their services (e.g. Silver Jubilee Home for the Aged requiring RM1 OOK every month in Penang). This has led to charity organizations either launching their own crude donation drive due to lack of fundraising knowledge or soliciting services from professionals. Nevertheless, associations with professional fundraisers are regarded as unhealthy by Datuk Lee Kah Choon, parliamentary secretary of Health Ministry as fees charged by these professionals are heavily exorbitant which can be as high as 50-70% of total donation raised (Foong and Ng, 2007). This study is therefore carried out to provide better understanding into public donation intention in Penang, in-line with Reis (1998) observation that individuals are the prime contributors to charity giving (e.g. 75% of total 1997 donation in United States came from public donations). Ajzen (1991)'s Theory of Planned Behavior (TOPB) is applied as cornerstone of this study as it was found to be rarely used to in area of monetary donation despite being a widely adopted intention-behavior model (Bartolini, 2005; van der Linden, 2011 ). Present theoretical framework also extends TOPB model to include four more cognitive factors namely Trust, Problem Awareness, Egoism and Relationship leveraging on 8 key donation drivers identified through extensive literature review of over 500 charity researches by Bekkers and Wiepking (2007). This extended framework's consideration of cognitive factors is in-line with Social Cognitive Theory (Bandura, 1986)'s believe that cognition is significant in influencing behavior. In fact, Cheung and Chan (2000) further noted that social cognitive perspective is useful to describe donation behavior.